2017
DOI: 10.1242/bio.022335
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous AJAP1 associates with the cytoskeleton and attenuates angiogenesis in endothelial cells

Abstract: The adherens junction associated protein 1 (AJAP1, aka shrew-1) is presumably a type-I transmembrane protein localizing and interacting with the E-cadherin-catenin complex. In various tumors, AJAP1 expression is reduced or lost, including hepatocellular and esophageal squamous cell carcinoma, and glial-derived tumors. The aberrant expression of AJAP1 is associated with alterations in cell migration, invasion, increased tumor growth, and tumor vascularization, suggesting AJAP1 as a putative tumor suppressor. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Hötte et al found that AJAP1 is associated with the cytoskeleton in endothelial cells. 25 Tanaka et al 26 levels were inversely correlated with the levels of SRC in HCC cell lines and tissues, which verified our hypothesis shown in Figure 7. We also demonstrated effects on the downstream proteins E-cadherin…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hötte et al found that AJAP1 is associated with the cytoskeleton in endothelial cells. 25 Tanaka et al 26 levels were inversely correlated with the levels of SRC in HCC cell lines and tissues, which verified our hypothesis shown in Figure 7. We also demonstrated effects on the downstream proteins E-cadherin…”
Section: Discussionsupporting
confidence: 88%
“…Hötte et al. found that AJAP1 is associated with the cytoskeleton in endothelial cells . Tanaka et al pointed out the necessity of exploring the correlation between AJAP1 expression, a tumour‐recurrence predictor and EMT markers.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA-seq analysis revealed the putative tumor suppressor AJAP1 as the most highly expressed gene in fusion-positive lines. AJAP1 is a type-1 transmembrane protein that localizes and interacts with the E-cadherin-catenin complex and is involved in cellular processes such as cell migration and invasion by modulating adherens junctions and remodeling the ECM and cytoskeleton [ 52 ]. For example, in nonpolarized, highly migratory and invasive cells, AJAP1 interacts with the transmembrane glycoprotein CD147, an invasion-promoting protein [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adherens junctions associated protein 1 (AJAP1) is a type-I transmembrane protein that localizes and interacts with the E-cadherin-catenin complex. The endogenous AJAP1 is associated with the microtubule cytoskeleton and can attenuate sprouting angiogenesis by reducing endothelial migration and invasion capacities 47 .…”
Section: Discussionmentioning
confidence: 99%